Essential oil and bioactive compounds from Miogyne SP / Nor Hadiani Ismail and Asmah Alias - Ismail, Nor Hadiani; Alias, Asmah (Institute of Research, Development and Commercialization, Universiti Teknologi MARA, 2012)
The flora of Malaysia is generally considered as one of the richest flora in the world due to the constantly warm and uniformly humid climate. Considering that Malaysia has about 12 000 species of flowering plants of which is about 1300 have potential as medicinal agent (Burkill, 1935), the potential of drug discovery from Malaysian plants is very good. The huge diversity of Malaysian flora means that researchers can obtain various samples to analyze and evaluate in drug discovery screen or bioassays.